Impact of feature selection and kernel functions in classification for image acquisition forensics - Chua, Shaun Ming Jun. (2012)
With the increased availability of digital image from the Internet and easy to get image editing software, the origin or the image source for these images have become a serious concern. The paramount value of the pictures lies in their ability to offer graphic credibility and convincing proof of facts in search of truth, which should be the ultimate goal of all litigation. To keep the integrity and ensure the accuracy and reliability of digital data, it is important to help establish a solid model on the characteristic of images obtained directly from its original source. This, in turn, will facilitate tampering forensics to determine if there has been any additional editing and processing applied to an image after it leave the source.